Room Temperature NH3 Selective Gas Sensors Based on Double-Shell Hierarchical SnO2@polyaniline Composites - Yuan Qu; Haotian Zheng; Yuhua Lei; Ziwen Ding; Siqi Li; Song Liu; Wei Ji (Sensors, 2024)
Morphology and structure play a crucial role in influencing the performance of gas sensors. Hollow structures, in particular, not only increase the specific surface area of the material but also enhance the collision frequency of gases within the shell, and have been studied in depth in the field of gas sensing. Taking SnO2 as an illustrative example, a dual-shell structure SnO2 (D-SnO2) was prepared. D-SnO2@Polyaniline (PANI) (DSPx, x represents D-SnO2 molar content) composites were synthesized via the in situ oxidative polymerization method, and simultaneously deposited onto a polyethylene terephthalate (PET) substrate to fabricate an electrode-free, flexible sensor. The impact of the SnO2 content on the sensing performance of the DSPx-based sensor for NH3 detection at room temperature was discussed. The results showed that the response of a 20 mol% D-SnO2@PANI (DSP20) sensor to 100 ppm NH3 at room temperature is 37.92, which is 5.1 times higher than that of a pristine PANI sensor. Moreover, the DSP20 sensor demonstrated a rapid response and recovery rate at the concentration of 10 ppm NH3, with response and recovery times of 182 s and 86 s.